Optimizing Tourist Satisfaction at Mount Bromo: A Sentiment Analysis Approach - Alvin Lukita; Melissa Indah Fianty (Universitas Islam Raden Rahmat, Malang, 2024)
In the era of ever-growing globalization, information technology is the main driver of transformation in various sectors of life. Information technology plays an important role in the progress of the tourism sector by offering easy access to information. The Mount Bromo tourist attraction is one of the popular destinations in Indonesia which attracts many visitors every year. The large number of comments from visitors to the Mount Bromo tourist attraction on the Trip Advisor site means that there is no filtering of information or reviews so that the Mount Bromo National Park management does not know whether there are many positive or negative reviews. The method used in the research is the Naive Bayes method it produces an accuracy value of 0.85%. This accuracy value can be used to classify visitor review data at the Mount Bromo tourist attraction. The conclusion is that there are many positive reviews.